2015
DOI: 10.1093/ageing/afv154
|View full text |Cite
|
Sign up to set email alerts
|

Observational cohort study: deprivation and access to anti-dementia drugs in the UK

Abstract: Background: UK National Dementia Strategies prioritise fair access to dementia treatments for the whole population. We investigated for the first time inequalities in NHS national dementia prescribing and how they have varied between UK countries and over time.Method: we investigated the association between Townsend deprivation score and anti-dementia drug prescribing in 77,045 dementia patients from UK primary care records from 2002 to 2013.Results: we included 77,045 patients with recorded dementia diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
70
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 19 publications
6
70
1
3
Order By: Relevance
“…Sixth, the international literature emphasizes the relationship between AD and high costs 25 , which could lead to less Another important finding of the present study was the clear disparity in the distribution of medications in Brazil, a result that has also been confirmed by other international studies such as one conducted in Australia, which found that geographic isolation and lower socioeconomic conditions were associated with lower rates of prescriptions of cholinesterase inhibitors 27 , and another in the United Kingdom, which found that rates of prescriptions of cholinesterase inhibitors diminished as inequality and financial needs increased 28 .…”
supporting
confidence: 83%
“…Sixth, the international literature emphasizes the relationship between AD and high costs 25 , which could lead to less Another important finding of the present study was the clear disparity in the distribution of medications in Brazil, a result that has also been confirmed by other international studies such as one conducted in Australia, which found that geographic isolation and lower socioeconomic conditions were associated with lower rates of prescriptions of cholinesterase inhibitors 27 , and another in the United Kingdom, which found that rates of prescriptions of cholinesterase inhibitors diminished as inequality and financial needs increased 28 .…”
supporting
confidence: 83%
“…Lower levels of education and worse physical health, which are strongly linked to deprivation, are associated with a greater dementia risk [2, 3]. Among people with dementia those from more deprived areas, women and older people are relatively less likely to receive anti-dementia drugs [18]. We aimed to investigate whether there are also social inequalities in physical preventative healthcare provision and psychotropic drug prescribing among people with dementia, and to compare these outcomes in people with and without dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Since the indices for area deprivation have been widely associated with inequalities in access to care and services, people with dementia living in deprived areas might have limited support from local health and social care systems. Recent analyses of UK primary care data suggested that people with dementia in least deprived areas were 25% more likely to be prescribed antidementia drugs such as cholinesterase inhibitors and memantine than the most deprived but did not find any variation in receipt of healthcare and psychotropic medication across deprivation levels . On the other hand, Dementia Atlas, an interactive website developed to monitor indicators for primary, secondary, and tertiary care in England, reveals disparity of care and different completion rates of the annual care review across areas .…”
Section: Discussionmentioning
confidence: 99%